Glycerol and Maleic Anhydride-Based Acrylic Polyester: A Solution for Greener Photocurable Resins for 3D Printing of Renewable Materials - dos Santos, Gabriel I. [UNESP]; Gaglieri, Caroline [UNESP]; Alarcon, Rafael T.; de Moura, Aniele; dos Santos, Fernanda B. [UNESP]; Bannach, Gilbert [UNESP] (American Chemical Society (ACS), 2025)
The three-dimensional (3D) printing field has emerged as a powerful tool for manufacturing complex design materials, becoming a solution for technological issues, and the depletion of nonrenewable sources brings the urgency of a sustainable additive manufacturing way to produce materials. In this sense, a potentially 100% renewable glycerol and maleic anhydride-based acrylic polyester (PPH) was synthesized, requiring 8 min of reaction after optimization. Then, varied levels of potentially biobased resins were formulated by mixing the renewable polyester, 2-hydroxyethyl methacrylate (as a reactive diluent), and the photoinitiator diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide. These formulated resins were then applied in a digital light processing 3D printer. The resins with PPH content above 50.0% presented suitable viscosity for 3D printing, while the formulation with a lower viscosity value favors printability and resolution for complex design objects. The 3D-printed objects were characterized regarding thermal and mechanical properties, which were verified to be affected by monomer conversion and the amount of PPH in the formulation. High and intermediate amounts of renewable polyester resulted in flexible materials, whereas reducing PPH content produced rigid materials with a substantial increase in hardness. Finally, it is suggested that the difference in reactivity of PPH and HEMA led to the formation of a semi-interpenetrating polymer network. This sustainable approach enabled the production of potentially greener photocurable resins for additive manufacturing.